(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
This research presents a stable numerical scheme for the Fitzhugh-Nagumo time-fractional partial differential equation using finite differences method, and L1-approximation for the fractional operator. The nonlinear term has been treated by Taylor approximation of zero degree. The unconditional stability and consistency for the proposed scheme have been theoretically proven, and the convergence have been numerically studied. We provide some experiments and comparisons that supports the theoretical results and shows the efficiency of the proposed scheme.